Competency-Based Training for Business and Management’s Vocational Teachers in East Kalimantan - Wijayani*, Dahyang Ika Leni; Kusno, Hendra Sanjaya; Finanto, Hasto (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
As evidence of their proficiency, Accounting Vocational School graduates are required to possess a TA Junior Competency Certificate. There is only one certified accounting technician teacher in Balikpapan now. This service attempts to address this problem by certifying accounting teachers with professional skills. It is envisaged that as SMK Accounting teachers become certified, SMK graduates’ competence will rise as well. The program provided as part of this community service aims to assist in resolving current issues by providing: (1) offline training to get ready for junior accounting technician competency exam; and (2) support during the exam. Forty-five teachers from vocational schools in East Kalimantan participated in this program. Overall, 56% of participants reported feeling extremely satisfied, and up to 44% reported feeling satisfied and assisted by the training. According to the feedback from this program, participants thought that more training time was necessary, particularly for computer accounting application schemes.